Sistem Informasi PPDB Dengan Menerapkan Metode Simple Additive Weight (SAW) Dalam Sistem Pendukung Keputusan Pemilihan Sekolah - Putra, Candra Novaliandi Pranata; Ritonga, Alven Safik (Journal of System Engineering and Technological Innovation, 2024)
This research proposes and implements a web-based New Student Admission Information System (PPDB) using the Simple Additive Weight (SAW) method as a decision support system for school selection. The case study was conducted at the Lidah Kulon I/464 Surabaya Elementary School. The background of this research is driven by the significant impact of information technology advancements in the education sector. Lidah Kulon I/464 Surabaya Elementary School, as an educational institution committed to achieving excellence, discipline, faith, science and technology (IPTEK), as well as environmental awareness, strives to reduce paper usage in the new student registration process by transitioning to a more efficient administrative information system. The results of the tests state that the system has succeeded in various aspects, including the use of the Certainty Factor Method, diagnosis menu, information menu, login menu, and others. The conclusion of this research is that the system has been implemented successfully, supporting the efficiency of the PPDB process, and providing easy access to users. System development recommendations for the future include flexibility without hard coding, more comprehensive user management, the development of a more advanced school selection system, more accurate entrance fee calculations, and considerations for seasonal factors and school promotions. Keyword: PPDB Information System, Simple Additive Weight (SAW), Method Student Registration, Efficiency Educational Administration